(untitled) (Analysis in Theory and Applications, 2018)
This paper is sequel to the authors paper [18]. By using the generalized Burchnall-Chaundy operator method, the authors are aiming at deriving certain decomposition formulas for some interesting special cases of Kamp00e9 de F00e9riets series of double hypergeometric series F^p:q;k_l:m;n.